TRANSFORMATIONAL LEADERSHIP MANAGEMENT AT STATE ISLAMIC JUNIOR HIGH SCHOOL - Usamah Azzuhri; Zaki Ulien Nuha (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to analyze the application of transformational leadership management by madrasah principals and its contribution to the realization of an excellent madrasah at MTs N 2 Kota Kediri. The study uses a descriptive qualitative approach to gain an in-depth understanding of transformational leadership practices in the natural context of madrasahs. The research subjects included the principal, teachers, staff, and students who were selected purposively based on their direct involvement in the leadership and educational management processes. Data were collected through in-depth interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show that transformational leadership at MTs N 2 Kota Kediri is carried out in an integrated manner with managerial functions and is based on religious values. The madrasah principal acts as a driver of change through exemplary behavior, inspirational motivation, intellectual stimulation, and consistent individual attention. The application of this leadership has an impact on strengthening the school culture, increasing teacher motivation and commitment, creating a safe and conducive learning environment, and developing the character and achievements of students. This study concludes that transformational leadership management contributes significantly to building an excellent madrasah that not only emphasizes academic achievement but also character building, educator quality, and educational quality sustainability. Keywords: Transformational Leadership; Leadership Management; Excellent Madrasah; Madrasah Principal; Islamic Education Abstrak Penelitian ini bertujuan untuk menganalisis penerapan manajemen kepemimpinan transformasional kepala madrasah serta kontribusinya terhadap terwujudnya madrasah unggul di MTs N 2 Kota Kediri. Penelitian menggunakan pendekatan kualitatif deskriptif untuk memperoleh pemahaman mendalam mengenai praktik kepemimpinan transformasional dalam konteks alamiah madrasah. Subjek penelitian meliputi kepala madrasah, guru, staf, dan murid yang dipilih secara purposive berdasarkan keterlibatan langsung dalam proses kepemimpinan dan pengelolaan pendidikan. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional di MTs N 2 Kota Kediri dijalankan secara terintegrasi dengan fungsi manajerial dan berlandaskan nilai-nilai religius. Kepala madrasah berperan sebagai penggerak perubahan melalui keteladanan, motivasi inspiratif, stimulasi intelektual, dan perhatian individual yang konsisten. Penerapan kepemimpinan tersebut berdampak pada penguatan budaya sekolah, meningkatnya motivasi dan komitmen guru, terciptanya lingkungan belajar yang aman dan kondusif, serta pengembangan karakter dan prestasi peserta didik. Penelitian ini menyimpulkan bahwa manajemen kepemimpinan transformasional berkontribusi signifikan dalam membangun madrasah unggul yang tidak hanya menekankan capaian akademik, tetapi juga pembinaan karakter, kualitas pendidik, dan keberlanjutan mutu Pendidikan. Kata Kunci: Kepemimpinan Transformational; Manajemen Kepemimpinan; Madrasah Unggul; Kepala Madrasah; Pendidikan Islam